The use of small-sided games to assess skill proficiency in youth soccer players: a talent identification tool. Issue 3 (3rd July 2018) - Bennett, Kyle J. M.; Novak, Andrew R.; Pluss, Matthew A.; Stevens, Christopher J.; Coutts, Aaron J.; Fransen, Job
ABSTRACT: Purpose: This study adopted an exploratory approach to investigate the use of small-sided games as a talent identification tool to determine youth soccer players' skill proficiency.Methods: A total of 73 male youth soccer players (age = 13.3 ± 1.2 years) were subdivided into two groups in accordance with their playing level (high-level: n = 36, low-level: n = 37). Within their levels, players completed 4 vs. 4 small-sided games on a 30 × 20 m playing surface under two conditions (condition 1: 5 × 3 min, condition 2: 3 × 5 min). Attempted and completed skill involvements were analysed using retrospective video analysis. Skill proficiency was determined as the total completed involvements relative to amount attempted.Results: Repeated measures multivariate analysis of variance identified that high-level players displayed a significantly greater number of attempted and completed passes, touches, and total skill involvements compared with low-level players. Only the number of attempted passes and total involvements differed between conditions for high-level players. High-level players' total skill proficiency was significantly greater than their lower level counterparts.Conclusion: This study supports the use of small-sided games as a tool to assess soccer-specific skill proficiency, which coaches and sporting practitioners can apply in a talent identification setting.